Pengembangan Bahan Ajar Mata Kuliah Perkembangan Peserta Didik Berbasis CTL (Contextual Teaching and Learning) - Trisna Kusuma Wardani; Azmussya’ni (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This research aims to develop teaching materials for CTL-based student development courses for PGSD students in the third semester of Nahdlatul Ulama University of West Nusa Tenggara (UNU NTB). Based on initial observations, it shows that there is no structured teaching material as a guide for lecturers in teaching student development courses. So it is necessary to develop teaching materials for CTL-based courses. CTL is one of the learning approaches that requires students to be active and experience direct learning, so that learning becomes more meaningful. This research is a development research (R&D), with a simplified Borg and Gall development model. Based on the results of the research conducted, it can be concluded that learning with teaching materials for CTL-based student development courses has been developed in accordance with development procedures. The feasibility of teaching materials for students is reviewed after learning is carried out using teaching materials. Student learning outcomes increased with the number of students who completed 25 people with the highest score of 100 and the number of students who did not complete was 2 people with the lowest score was 50, with an average number of 80.55, while the classical completeness score was 92%. Student responses to the teaching materials of the student development course are said to be very responsive, with an average response percentage of "yes" of 95.62% and "no" of 8.02%. So that the teaching materials for student development courses developed are suitable for use in the learning process at the elementary level.